Effect of barium doping in Bi-Pb-Sr-Ca-Cu-O ceramics superconductors - Halim, S. A.; Mohamed, S. B.; Azhan, H.; Khawaldeh, S. A.; Sidek, H. A.A. (Elsevier, 1999)
The effect of barium doping on the superconductivity in Bi2Pb0.6Sr2Ca2-xBa xCu3Oδ system has been investigated by resistivity, ac susceptibility measurements and X-ray diffraction analysis. Barium was incorporated in the calcium site with x ranging from 0.00 to 0.10. The temperature dependence of electrical resistance and ac susceptibility measurements were made on these samples. The nature of the temperature dependence of the resistance curves indicates the presence of a superconducting transition between grains coupled by weak links. From the XRD data, it is observed that the volume percentage of the 2223 phase decreases with the increasing barium concentration. The presence of low Tc phase is also visible in the real component, χ′, of the susceptibility data, while the imaginary component, χ″, show a shift towards lower temperature in the intergranular coupling peak, Tp, as the barium concentration increases. Barium doping does not enhance the Tc zero but gradually decreases its value from 104 K to 88 K for x=0.00 to x=0.10 respectively.